The Effect of Teamwork and Work Discipline on Employee Performance at Bank BTPN KCP Pandeglang - Afrizy, Mochamad Kemal; Rachman, Nono Arief; Syiarudin, Asep (International Conference on Business Management and Accounting, 2023)
The purpose of this study is how teamwork and work discipline affect employee performance, the research method uses primary data by distributing questionnaires to respondents then the data is processed using correlation coefficients, determinant coefficients, and hypothesis testing. Research proves that the result of the correlation analysis of teamwork is 0.949 which means that there is a positive and strong influence between teamwork and employee performance, while the result of the correlation analysis of work discipline is 0.795 meaning that there is a positive and strong influence between work discipline and employee performance. The simultaneous correlation test result is 0.762. This shows that there is a simultaneous positive and strong influence between teamwork and work discipline on employee performance. Determinant coefficient analysis shows that teamwork and work discipline contribute as much as 81.3% to employee performance. The t value of the Teamwork variable is 1.094, which means that t count <t table (1.094<1.685) with a significance of 0.281 in other words Teamwork has no effect on Employee Performance. The t value of the Work Discipline variable is 2.328 which means that t count > t table (2.328> 1.685) with a significance of 0.031 in other words Work Discipline affects Employee Performance. The F value obtained was 5.017 with a significance level of 0.012. Because the significant level is less than 0.05, it can be said that Teamwork and Work Discipline have a simultaneous effect on Employee Performance.